2019
DOI: 10.1093/aob/mcz170
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of salinity and inundation on native Spartina foliosa, invasive S. densiflora and their hybrid from San Francisco Estuary, California

Abstract: Background and Aims Sea Level Rise (SLR) associated with climate change is intensifying permanent submersion and salinity in salt marshes. In this scenario, hybridization between native and invasive species may result in hybrids having greater tolerance of abiotic stress factors than their parents. Thus, understanding the responses of native and invasive halophytes and their hybrids to interacting physiological stresses imposed by SLR is key to native species conservation. We analyzed how sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 79 publications
2
13
0
Order By: Relevance
“…Other studies have found relatively high levels of salt tolerance in hybrids, for example, the hybrid sunflower Helianthus paradoxus had higher survival and biomass than either parent species under highly saline conditions, and is considered to be transgressive for salt tolerance relative to its progenitors (Welch & Rieseberg, 2002) (Karrenberg et al., 2006). In another example, the hybrid of Spartina densiflora and S. foliosa appears better able than its parent species to deal with the stressors of flooding and salinity associated with sea level rise (Gallego‐Tévar et al., 2020). The relatively high production of ramets by T. × glauca provides an important mechanism for clonal expansion within a coastal site.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found relatively high levels of salt tolerance in hybrids, for example, the hybrid sunflower Helianthus paradoxus had higher survival and biomass than either parent species under highly saline conditions, and is considered to be transgressive for salt tolerance relative to its progenitors (Welch & Rieseberg, 2002) (Karrenberg et al., 2006). In another example, the hybrid of Spartina densiflora and S. foliosa appears better able than its parent species to deal with the stressors of flooding and salinity associated with sea level rise (Gallego‐Tévar et al., 2020). The relatively high production of ramets by T. × glauca provides an important mechanism for clonal expansion within a coastal site.…”
Section: Discussionmentioning
confidence: 99%
“…It was calculated that a global SLR greater than 26 cm by 2100 would likely be greater than some ecosystems' abilities to accrete sediment and increase elevation over this period of time (Macreadie et al, 2017). In addition, SLR can also have synergic effects with changes in the salinity and inundation conditions which can lead to reduced fitness for some marsh species (Gallego-Tévar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual reproduction is a critical life history process that increases the genetic diversity and ability of plants to respond to environmental changes, increases their capacity for long-distance dispersal, and supports long-term persistence and conservation of plant populations (Van Drunen and Dorken, 2012). The capacity to maintain sexual reproduction is especially relevant as plants are exposed to rising levels of synergistic environmental stress factors imposed by global warming (Gallego-T evar et al, 2019a). Climate scientists have documented increasingly warmer conditions at the Earth's surface in each of the last three decades than in any preceding decade since 1850 (IPCC 2013).…”
Section: Introductionmentioning
confidence: 99%